Folic Acid Attenuates N-Methyl-N’-Nitro-N-NitrosoguanidineInduced Gastric Mucosal Injury in Rats - Caiting Peng; Li Wang; Yuan Liang; Li Che; Rongjing Sun; Jia Yu; Jiamin Gong; Dandan Wang; Suizhi Cheng; Qingqing Yang; Tao Jing; Zhenzhong Liu (The Turkish Journal of Gastroenterology)
Background/Aims: N-Methyl-N’-nitroso-N-nitrosoguanidine (MNNG) is suspected to increase the risk of developing stomach cancer. Folic acid (FA) is familiar with decreasing inflammation. We expected that FA would protect against MNNG-induced gastric mucosal injury.